Trust in governance networks: its impacts on outcomes - Klijn, Erik-Hans; Steijn, Bram; Edelenbos, Jurian (2010)
Governance networks are characterized by complex interaction and decision making, and much uncertainty. Surprisingly, there is very little research on the impact of trust in achieving results in governance networks. This article asks two questions: (a) Does trust influence the outcomes of environmental projects? and (b) Does active network management improve the level of trust in networks? The study is based on a Web-based survey of respondents involved in environmental projects. The results indicate that trust does matter for perceived outcomes and that network management strategies enhance the level of trust. - Reproduced.
Keywords: Network analysis